Educação comparada: perspectivas teóricas e investigações - Martha Aparecida Santana Marcondes (EccoS – Revista Científica)
The globalization process has promoted deep changes in society and within the academic world. Due to the growing interdependence among countries, there has been no more sense in traditional concepts towards nation and society neither towards exclusivity in ideas: each nation needs to know its partners realities. Presently, it is emphasized that one must deal with cultural plurality and multiethnicity. It is searched, through Education, the humanization of social changes. In this context, it is emphasized that compared studies in Education and compared education start being valued as a meaningful element for a better comprehension of the globalization process influences on educative politics. This paper analyzes some theoretical approaches of compared education and shows its contribution to the school practice